The Predictive Role of Cognitive Emotion Regulation Strategies in Marital Satisfaction and Job Burnout among Nurses - A Easazadeh (Iran University of Medical Sciences, 2016)
Abstract Background & aim: Emotion regulation strategies are so important in the job burnout and marital satisfaction. Here we investigate the relationships between cognitive emotion regulation strategies, job burnout and marital satisfaction among female nurses. Material & Methods: In this descriptive-correlation study, participants included 140 female nurses were practitioner in hospitals in Ardabil (including nurses, nursing technicians and nursing assistants and were selected through convenience sampling and respect to inclusion and exclusion criteria. To gather the data, the short form of Cognitive Emotion Regulation Strategies questionnaire, Job Burnout and Mslesh Marital Adjustment questionnaires were applied. Data were analyzed by descriptive statistics and inferential statistics including correlation and stepwise regression. Results: The results of data analysis indicated that acceptance strategies, positive reappraisal and rumination strategies are able to significantly predict marital satisfaction and blaming others. Acceptance and rumination strategies have significant ability to predict job burnout in women in nursing. Also, between marital satisfaction, job burnout and maladaptive emotion regulation strategies was a significant inverse relationship, and between marital satisfaction, job burnout and adaptive emotion regulation strategies was a significant direct relationship. Conclusion: The results of this study revealed the relationship between cognitive emotion regulation strategies, marital satisfaction and job burnout among nurses. It is suggested that emotion regulation strategies should be used in educational and prevention programs for nurses as an effective factor associated with marital satisfaction and job burnout.